THE ART OF INTERVIEWING - Painter, Desmond (PINS-Psychology in Society, 2025)
Denis, Philippe & Ntsimane, Radikobo (eds) (2008) Oral history in a wounded country: Interactive interviewing in South Africa. Pietermaritzburg: Universtiy of KwaZulu-Natal Press. ISBN 978-1-86914-147-9. Pages vii + 196. Students of psychology should take note of this book; lecturers of methodology modules in the discipline should too. Published in 2008 already, this edited volume seems to have disappeared under the radar somewhat – at least in psychology. It is as if our exposure to research methodology texts is still mediated through disciplinary formations (or should I say fortifications?!). This is a pity, because even though not written by and for psychologists, many of the issues discussed in this book are pertinent to psychologists – to researchers, community practitioners and psychotherapists alike. It certainly belongs on the methods and methodology reading lists we provide our students with.